Highly efficient monovalent ion transport enabled by ionic crosslinking‐induced nanochannels. Issue 11 (12th July 2022) - Zhang, Yiren; Lin, Yuqing; Ying, Jiadi; Zhang, Wei; Jin, Yan; Matsuyama, Hideto; Yu, Jianguo
Abstract: Charge‐governed ion transport is of significant importance to industrial development, and advanced membrane materials with fast and selective ionic transport are essential components. In cell membranes, ionic transport is mainly determined by the charge‐governed protein channels, representing an architecture with functional differentiation. Inspired by this, a novel class of membranes was developed by ionically crosslinking sulfonated (poly[ether ether ketone]) and quaternized poly(2, 6‐dimethyl‐1, 4‐phenylene oxide) to construct the cationic conductive biomimetic nanochannels. Ionic crosslinking was tailored to realize nanophase separation and efficient ion transport mainly based on surface chemistry without altering the scaffold feature of polymeric pore channels. The best‐performing ionic crosslinking membrane exhibited a high ionic permeation (2.23 mol·m −2 ·h −1 for K + ) and high cationic selectivity (7.91 for K + /Mg 2+ ), which were comparable with the commercial monovalent cation permselective CIMS membrane, owing to the negligent surface resistance toward monovalent cations but strong positively charged repulsion against divalent cations.